이종 장기이식 및 조직 공학을 위한 Alpha gal 유전자 결손돼지 (1, 3-galactosyltransferase-deficient pigs)에서 혈관내피세포(aortic endothelial cells)의 구축 - 옥선아; 임맑음; 김영지; Imran Ullah; 신유리안나; 김영임; 오건봉; 황성수; 허태영; 이승훈; 임기순 (Journal of animal reproduction & biotechnology (Online), 2017)
Tissue engineering (TE) has been developed to create functional organs and tissue by combining 3D matrix and cells in vitro. Vascularization and angiogenesis are utmost important for supply of nutrients and oxygen in tissue engineered organs. The present study was performed to isolate and characterize primary endothelial cells (EC) from aorta of alpha 1, 3-enzyme galactosyltransferase knock out (GalT KO) pig, to minimize immune rejection and analyze body immune system for future xenotransplantation studies. Isolation of primary EC from aorta were performed by incubation with dispase for 8-10 min at 37℃. Primary EC were cultured in EC growth medium on different extra cellular matrix (ECM), either collagen or gelation. Primary EC exhibits morphological characteristics and showed positive expressions of EC specific marker proteins i.e. PECAM1, KDR and VWF despite of their ECM surface; however, on collagen based surface they showed increase in mRNA level analyzed by qPCR. Primary EC cultured on collagen were sorted by flow cytometer using KDR marker and cultured as KDR positive cells and KDR negative cells, respectively. KDR positive cells showed dramatically increased in PECAM1 and VWF level as compared to KDR negative cells. Based on the above results, primary EC derived from GalT KO are successfully isolated and survived continuously in culture without becoming overgrown by fibroblast. Therefore, they can be utilize for xeno organ transfer, tissue engineering, and immune rejection study in future. KCI Citation Count: 0